Mapping the Research Landscape of QRIS in Indonesia: A Bibliometric and Content Analysis from 2019 to 2025 - Hanifah, Sarah Hana; Nurhidayati (Journal of Islamic Economics Literatures, 2025)
This study aims to map the academic research landscape on QRIS (Quick Response Code Indonesian Standard) from 2019 to 2025, identifying key themes, trends, and factors influencing its adoption and implementation in Indonesia. A bibliometric and content analysis was conducted on 35 Scopus-indexed articles using VOSviewer. The study focused on co-occurrence mapping and thematic clustering to identify dominant research areas.The analysis revealed six major research clusters: QRIS adoption, payment system, perceived impact, behavioral use, innovation in tourism, and user acceptance. The findings show that although the number of studies is still limited, interest in QRIS research is growing steadily, particularly in its role within MSMEs and tourism sectors. Key drivers include perceived usefulness, ease of use, trust, and technological readiness, often analyzed through TAM, UTAUT, and TRAM frameworks. This research highlights the critical need for digital literacy, infrastructure development, and supportive policy to ensure inclusive and sustainable adoption of QRIS. It also underscores the importance of interdisciplinary research efforts and academic contributions in shaping the future of QRIS and Indonesia’s digital payment transformation.